A reflexive thematic analysis exploring the experiences of undergraduate women in STEM in Bangladesh - Parinda Rahman (Springer, 2024)
Abstract Globally, a significant gender gap is reported in the enrolment of women in Science, Technology, Engineering, and Mathematics (STEM). Bangladesh reports one of the lowest female stakeholder percentages in STEM but has increased demand for skilled STEM professionals. Therefore, this qualitative study explores the experiences of undergraduate women in STEM in Bangladesh. Seven female undergraduate students were recruited using purposeful sampling, and a semi-structured interview was conducted. Reflexive thematic analysis, along with a phenomenological approach, was utilized for data analysis to gain a better understanding of their experiences. The four key themes that emerged were the gendered nature of interactions, the impact of societal barriers, underrepresentation and role models, self-identity, and psychological outcomes. The findings suggested multiple factors like gender-biased interactions in classrooms, lack of access to STEM resources, and lack of female role models negatively impacted students' academic experiences. Moreover, poor self-esteem in female students contributed to imposter syndrome and heightened career anxiety.